Missing elimination via membrane vesicle shedding contributes to the diminished calcium sensitivity of listeriolysin O - Maurer, Jana; Hupp, Sabrina; Pillich, Helena; Mitchell, Timothy J.; Chakraborty, Trinad; Iliev, Asparouh I. (Scientific reports, 2018)
The lytic capacity of cholesterol-dependent cytolysins is enhanced in the extracellular calcium-free environment through a combination of limited membrane repair and diminished membrane toxin removal. For a typical neurotoxin of the group, pneumolysin, this effect has already been observed at reduced (1 mM) calcium conditions, which are pathophysiologically relevant. Here, we tested another neurotoxin of the group, listeriolysin O from L. monocytogenes, active in the primary vacuole after bacterium phagocytosis in host cells.